Large In Situ Shear Test Box for Mine Waste Dump - Rai R.; Shrivastva B.K. (My University, 2025)
Shear strength of the dump material is very important in the stability analysis of slope. Determination of shear strength of dump or vegetated dump is very complicated and also requires large size of specimen so that it represents the true behaviour of dump mass with and without vegetation. Large size shear box (1.5 × 1.5 × 0.75 m) and small shear boxes (0.3 × 0.3 × 0.15 m) have been fabricated and used for the present study. Various types of plants have been grown in the mine waste dump in the laboratory. The grasses increased cohesion of the dump mass up to 27 kPa whereas the shrubs increased the cohesion up to 32 kPa in given conditions. The increased cohesion depends on the depth of root and age of tree. It generally varies from 10 to 80 kPa or more depending on the age of the tree. © 2012, The Institution of Engineers (India).